2017
DOI: 10.1111/cea.12916
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal antibiotics and atopic dermatitis among 18‐month‐old children in the Danish National Birth Cohort

Abstract: Prenatal exposure to antibiotics throughout pregnancy was associated with an increased risk of atopic dermatitis but only within the first 18 months of life among children born by atopic mothers. The clinical usefulness of this finding must rest on corroboration in independent data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 38 publications
3
58
0
1
Order By: Relevance
“…To the editor, Prenatal antibiotic exposure has been suggested to be a risk factor for childhood allergic disease, possibly by affecting the development of a healthy and diverse microbiome, which is important for immune maturation. [1][2][3] Atopic dermatitis (AD) is often the first manifestation of the so-called "atopic march" and has a prevalence of over 10% among children in many developed countries. 4 We aimed to investigate the association between prenatal antibiotic exposure and AD at age 1 in the Japan Environment and Children's Study (JECS).…”
Section: No Association Between Prenatal Antibiotic Exposure and Atopmentioning
confidence: 99%
“…To the editor, Prenatal antibiotic exposure has been suggested to be a risk factor for childhood allergic disease, possibly by affecting the development of a healthy and diverse microbiome, which is important for immune maturation. [1][2][3] Atopic dermatitis (AD) is often the first manifestation of the so-called "atopic march" and has a prevalence of over 10% among children in many developed countries. 4 We aimed to investigate the association between prenatal antibiotic exposure and AD at age 1 in the Japan Environment and Children's Study (JECS).…”
Section: No Association Between Prenatal Antibiotic Exposure and Atopmentioning
confidence: 99%
“…However, in a well-designed sibling-control study, Mulder et al [61] found prenatal antibiotic use to be predictive of childhood asthma even compared to sibling controls. Although some studies show influence regardless of trimester of maternal antibiotic use [57], this study found the influence to be more profound when antibiotic use occurs during the third trimester [61]. Although more research is needed to determine whether timing is crucial, multiple lines of evidence suggest the maternal microbiota during pregnancy plays a key role in preventing an allergy-prone immune phenotype in infants.…”
Section: Maternal Microbiota During Pregnancy and Offspring Immune-rementioning
confidence: 56%
“…More direct evidence for the influence of maternal microbiota during pregnancy on offspring atopic disease is antibiotic use during pregnancy, which can cause prolonged alterations to the microbiota and their metabolites [56]. In a Danish birth cohort, the use of prenatal antibiotics was associated with increased odds of atopic dermatitis at 18 months of age in infants of mothers with atopy [57]. In addition, in children aged 2-10 years, maternal use of any antibiotics during pregnancy was associated with a 1·3-fold increased risk of asthma in the offspring [95% confidence interval (CI) = 1·21-1·42] ( [58]).…”
Section: Maternal Microbiota During Pregnancy and Offspring Immune-rementioning
confidence: 99%
“…Early exposure to dogs has been reported to decreases the risk of asthma, 49,50 and Wegienka et al have now proposed that there are subgroup differences (race, gender and delivery mode) in the association. 55 Travelling is another risk factor that may be associated with microbiota and also with socioeconomic status. Simoneti and colleagues have reported in Clinical and Experimental Allergy that allergic sensitization to laboratory animals is more associated with asthma, rhinitis and skin symptoms than sensitization to common allergens.…”
Section: Early Risk Factor For Atopic Diseasementioning
confidence: 99%
“…54 Timm and colleagues though report an association between prenatal exposure to antibiotics and increased risk of atopic dermatitis (AD) in the first 18 months of life among children born to atopic mothers. 55 Travelling is another risk factor that may be associated with microbiota and also with socioeconomic status. Results from GINIplus and LISAplus show that early life travelling does not increase the risk of atopic outcomes until 15 years of age.…”
Section: Early Risk Factor For Atopic Diseasementioning
confidence: 99%